Circulating histone signature of human lean metabolic-associated fatty liver disease (MAFLD) - Buzova, Diana; Maugeri, Andrea; Liguori, Antonio; Napodano, Cecilia; Lo Re, Oriana; Oben, Jude; Alisi, Anna; Gasbarrini, Antonio; Grieco, Antonio; Cerveny, Jan; Miele, Luca; Vinciguerra, Manlio (Clinical epigenetics, 2020)
BACKGROUND: Although metabolic associate fatty liver disease (MAFLD) is associated with obesity, it can also occur in lean patients. MAFLD is more aggressive in lean patients compared to obese patients, with a higher risk of mortality. Specific biomarkers to diagnose differentially lean or overweight MAFLD are missing. Histones and nucleosomes are released in the bloodstream upon cell death. Here, we propose a new, fast, imaging and epigenetics based approach to investigate the severity of steatosis in lean MAFLD patients. RESULTS: A total of 53 non-obese patients with histologically confirmed diagnosis of MAFLD were recruited. Twenty patients displayed steatosis grade 1 (0-33%), 24 patients with steatosis grade 2 (34-66%) and 9 patients with steatosis grade 3 (67-100%). The levels of circulating nucleosomes were assayed using enzyme-linked immunosorbent assay, while individual histones or histone dimers were assayed in serum samples by means of a new advanced flow cytometry ImageStream(X)-adapted method. Circulating nucleosome levels associated poorly with MAFLD in the absence of obesity. We implemented successfully a multi-channel flow methodology on ImageStream(X), to image single histone staining (H2A, H2B, H3, H4, macroH2A1.1 and macroH2A1.2). We report here a significant depletion of the levels of histone variants macroH2A1.1 and macroH2A1.2 in the serum of lean MAFLD patients, either individually or in complex with H2B. CONCLUSIONS: In summary, we identified a new circulating histone signature able to discriminate the severity of steatosis in individuals with lean MAFLD, using a rapid and non-invasive ImageStream(X)-based imaging technology.
Keywords: histony; ImageStream; Male; hubenost; Adult; Epigenetics; dospělí; mužské pohlaví; metabolické nemoci; Severity of Illness Index; Metabolic Diseases; Lean MAFLD; Thinness; lidé; Liquid biopsy; ženské pohlaví; Humans; Metabolic health; Histones; ztučnělá játra; stupeň závažnosti nemoci; Fatty Liver; Female; lidé středního věku; Middle Aged